Strategies for the development of three dimensional scaffolds from piezoelectric poly(vinylidene fluoride) - Correia, D. M. (2016)
Cell supports based on electroactive materials, that generate electrical signal variations as a response to mechanical deformations and vice-versa, are gaining increasing attention for tissue engineering applications. In particular, poly(vinylidene ﬂuoride), PVDF, has been proven to be suitable for these applications in the form of films and two-dimensional membranes. In this work, several strategies have been implemented in order to develop PVDF three-dimensional scaffolds. Three processing methods, including solvent casting with particulate leaching and three- dimensional nylon, and freeze extraction with poly(vinyl alcohol) templates are presented in order to obtain three-dimensional scaffolds with different architectures and interconnected porosity. Further, it is shown that the scaffolds are in the electroactive β-phase and show a crystallinity degree of ~ 45 %. Finally, quasi-static mechanical measurements showed that an increase of the porous size within the scaffold leads to a tensile strengths and the Young’s modulus decrease, allowing tuning scaffold properties for specific tissues.